Perturbations of Monocyte Subsets and Their Association with T Helper Cell Differentiation in Acute and Chronic HIV-1-Infected Patients - Chen, Peng; Su, Bin; Zhang, Tong; Zhu, Xiaojing; Xia, Wei; Fu, Yan; Zhao, Guoxian; Xia, Huan; Dai, Lili; Sun, Lijun; Liu, Lifeng; Wu, Hao (Frontiers in Immunology, 2017)
Monocytes have been recently subdivided into three subsets: classical (CD14++CD16-), intermediate (CD14++CD16+), and non-classical (CD14+CD16++) subsets, but phenotypic and functional abnormalities of the three monocyte subsets in HIV-1 infection have not been fully characterized, especially in acute HIV-1 infection (AHI). In the study, we explored the dynamic changes of monocyte subsets and their surface markers, and the association between monocyte subsets and the IFN-γ, IL-4, IL-17 and TNF-α producing CD4+ T cells in acute and chronic HIV-1-infected patients. We found that, in the acute HIV-1-infected individuals, the frequency of the intermediate CD14++CD16+ monocyte subsets, the CD163 density and HLA-DR density on intermediate CD14++CD16+ monocytes, and plasma soluble form of CD163 (sCD163) were significantly higher than that in healthy controls. Intermediate CD14++CD16+ monocyte subsets and their HLA-DR expression levels were inversely correlated with the CD4+ T cell counts, and the intermediate CD14++CD16+ monocytes were positively correlated with plasma sCD163. In contrast to the non-classical CD14+CD16++ and classical CD14++CD16- monocyte subsets, the frequency of the intermediate CD14++CD16+ monocytes was positively associated with the frequency of IFN-γ and IL-4 producing CD4+ T cells in HIV-1-infected patients. Taken together, our observations provide new insight into the roles of the monocyte subsets in HIV pathogenesis, particularly during AHI, and our findings may be helpful for the treatment of HIV-related immune activation.